THE EFFECT OF TAXPAYER AWARENES AND FISKUS SERVICE ON PERFORMANCE OF TAX REVENUE WITH TAXPAYER COMPLIANCE AS INTERVENING VARIABLES - Dokman Marulitua Situmorang (Department of Management - Institut Shanti Bhuana, 2019)
Tax receipt is a major source of government financing to build the infrastructure and operating costs of a country. The population of this study was 87,846 individual taxpayers who were registered in KPP Pratama Medan city. The samples of this research are 100 individual taxpayers. This study discusses the influence of taxpayer awareness (X1) on the performance of tax revenue (Y), the direct influence of fiskus service (X2) on the performance of tax revenue (Y), Taxpayers Awareness (X1) on Taxpayer Compliance (Z) H0 is rejected so that there is a significant influence. Analysis of direct influence of Fiskus Services (X2) on Taxpayer Compliance (Z), H0 is accepted so as not to have a significant effect. Analysis of the indirect effect of taxpayer awareness (X1) on the performance of tax revenues (Y) through taxpayer compliance (Z) that taxpayer compliance (X1) on the performance of tax revenue (Y) significant effect through taxpayer compliance (Z) or in other words taxpayer compliance variable is an intervening variable or a mediation variable. Analysis of the indirect effect of Fiskus Services (X2) on the performance of tax revenues (Y) through taxpayer Compliance (Z) shows that Fiskus Service (X2) do is not have a significant effect on taxpayer compliance (Z) or in other words that taxpayer compliance variable is not an intervening variable or mediation variable.